THE EFFECT OF RED GINGER (ZINGIBER OFFICINALE VAR RUBRUM) COMPRESS ON THE PAIN LEVEL OF GOUT ARTHRITIS IN ELDERLY AT THE PARUNG KUDA HEALTH CENTER, SUKABUMI REGENCY - Iqbal, Aryl Alfath Muhamad; Wahyuni, Aisya Diza; Hayati, Yulianti; Isma, Dhiny (Jurnal Delima Harapan, 2025)
Background: Increased levels of uric acid in the blood, commonly referred to as hyperuricemia, result in the deposition of monosodium urate crystals in the joints, leading to gout. Nearly 80% of individuals aged 50 years and above experience joint problems, with gout being prevalent among the elderly. Objective: This study aims to determine the effect of red ginger compress on gout arthritis pain levels in elderly patients at the Parungkuda Public Health Center, Sukabumi Regency. Method: The research employed a quasi-experimental design with a one-group pretest-posttest approach. The sampling technique used was accidental sampling, involving 25 elderly respondents experiencing gout arthritis pain, all of whom were included as research samples. Results: The paired t-test results indicated a mean pain score of 3.18 before administering the red ginger compress and 2.09 after the intervention. The obtained p-value was 0.0001 (α < 0.005), demonstrating a statistically significant effect of red ginger compress in reducing gout arthritis pain in elderly patients. Conclusion: This study suggests increasing public awareness that red ginger compress can serve as a non-pharmacological technique for alleviating gout arthritis pain in elderly individuals.